Body Mass Index (BMI) assessment among Macau students: age group differences and weight management strategies - Ho, Walter King Yan; Ahmed, Md Dilsad; Leong, Chi Ian; Chan, Patrick; Van Niekerk, Rudolph Leon; Huang, Fan; Tian, Haili; Liu, Min; Chan, Nikon; Silva, João; Wong, Wilfred; Ho, Frederick K; et al. (Anthropological Review, 2017)
There is evidence that rapid weight gain during the first year of life is associated with being overweight later in life. Therefore, overweight tendencies need to be detected at an appropriate age, and suitable strategies need to be implemented for weight management to achieve optimal long-term health. The objective of this study was to investigate comparisons in BMI status and associated categories in male and female students over ten years in two phases, including 2008-2013 and 2009-2014. Weight and height data were collected to obtain BMI (Body Mass Index) over ten years in two phases. The first phase occurred from 2008 to 2013, and the second phase occurred from 2009 to 2014 in a population of 10846 school children (Males: 6970, 64.3%, and females: 3875, 35.7%) in Macau. Their ages ranged from 6 years old in 2008 to 11 years old in 2013. The same age range was observed in the second phase, i.e., 2009-2014. Statistical analyses included descriptive statistics, such as the mean, standard deviation, t-tests to determine gender differences (year-wise) and a Chi square test for independence to determine the relationship between BMI (Underweight, Standard, Overweight and Obese) and age groups. In the first phase (2008-2013), the findings indicated a higher BMI level among the male students than the female students across all age groups (2008 t = 5.24, 2009 t = 88.25, 2010 t = 11.32, 2011 t = 17.45, 2012 t = 19.70 and 2013 t = 19.92). In the second phase (2009-2014), a higher BMI level was found among the male students than the female students across all age groups (2009 t = 2.68, 2010 t = 2.886, 2011 t = 3.076, 2013 t = 4.228, and 2014 t = 2.405). The results of the two phases combined (2008 to 2014 and 2009 to 2014) revealed that male students in 2008 had a higher BMI level than their counterparts in 2009 in the two age categories (8 years t = 3.025 and 11 years t = 3.377). Female students in the second phase (2009-2014) showed a higher BMI level than their male counterparts (9 years, t = 3.151). The results indicate the need to have focused strategies and structured interventions for male students at the critical age range of 8 to 9 years old. The results of this study also imply the need for the delivery of suitable school intervention activities at the appropriate time. Specifically, the prevention of weight gain should start early in life to encourage the development of healthier behaviours and habits throughout childhood and later ages.